2021
DOI: 10.1093/geront/gnab144
|View full text |Cite
|
Sign up to set email alerts
|

Societal, Organizational, Relational, and Individual Perceptions of Sexual Violence Against Older Adults and Its Prevention: A Systematic Scoping Review

Abstract: Background and Objectives Older adults are not regarded as sexual and are widely excluded from sexual violence (SV) research, policies, and practice; little is known about SV against older adults and its prevention. Research Design and Methods An eight-database scoping review explored perceptions of SV against older adults, barriers to and solutions for prevention. Included were peer-reviewed and grey sources published since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Once studies were identified, their reference lists were reviewed for other potential studies for inclusion. A detailed audit trail [ 42 ] that included the thematic outcome columns was kept in Microsoft Excel, as well as a section for the interpretations and methodologies used in all searches, data extraction, and synthesis to increase this study’s transferability, confirmability, and dependability [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Once studies were identified, their reference lists were reviewed for other potential studies for inclusion. A detailed audit trail [ 42 ] that included the thematic outcome columns was kept in Microsoft Excel, as well as a section for the interpretations and methodologies used in all searches, data extraction, and synthesis to increase this study’s transferability, confirmability, and dependability [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is especially true for women and other members of nondominant groups in later life, as for example, women already face greater hardships than men, such as those owing to sexism and in turn, lower average pay, double standards at work and in the community, greater risks for emotional, physical, and sexual violence, and poorer treatment in the healthcare system (Chrisler et al, 2016). And the older women are, the greater their inequality (Chrisler et al, 2016), including with regard to risks for sexual violence (Bows & Westmarland, 2017), resulting trauma (Hand et al, 2021) and with this, greater health disparities and more poverty (Chrisler et al, 2016).…”
Section: Background: Structural Age-based and Intersectional Discrimi...mentioning
confidence: 99%
“…Structural discrimination, such as structural ageism (or widespread age-based oppression; Levy, 2022), racism (or systemic unjust treatment based on race; LaFave et al, 2022;Solomon et al, 2022), ableism (systemic oppression based on ability; Dhanani et al, 2022), sexism (systemic oppression owing to sex or gender) and heterosexism (systemic oppression of members of the LGBTQ+ community owing to sexual orientation) can ultimately impact health (Bows & Westmarland, 2017;Hand et al, 2021). Research has demonstrated that a greater reported frequency in encounters with these forms of prejudice have been predictive of more problems with physical health and wellness (Chrisler et al, 2016;Dhanani et al, 2022;LaFave et al, 2022;Levy, 2022).…”
Section: Background: Structural Age-based and Intersectional Discrimi...mentioning
confidence: 99%
See 2 more Smart Citations